Fatty Acid Signature Data of Chukchi Sea Polar Bears, 2008-2015 - Regehr, Eric V.; Wilson, Ryan R.; St. Martin, Michelle; Rode, Karyn D. (USGS Science Data Catalog, 2017)
This dataset contains fatty acid data expressed as mass percent of total fatty acids for Chukchi Sea polar bears.